Effects of Sulfonylureas on Periodontopathic Bacteria-Induced Inflammation. (July 2020) - Kawahara, Y.; Kaneko, T.; Yoshinaga, Y.; Arita, Y.; Nakamura, K.; Koga, C.; Yoshimura, A.; Sakagami, R.
Interleukin-1β (IL-1β) is an inflammatory cytokine produced by monocytes/macrophages and is closely associated with periodontal diseases. The NLRP3 inflammasome is involved in IL-1β activation through pro–IL-1β processing and pyroptotic cell death in bacterial infection. Recently, glyburide, a hypoglycemic sulfonylurea, has been reported to reduce IL-1β activation by suppressing activation of the NLRP3 inflammasome. Therefore, we evaluated the possibility of targeting the NLRP3 inflammasome pathway by glyburide to suppress periodontal pathogen-induced inflammation. THP-1 cells (a human monocyte cell line) were differentiated to macrophage-like cells by treatment with phorbol 12-myristate 13-acetate and stimulated by periodontopathic bacteria, Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, or Fusobacterium nucleatum, in the presence of glyburide. IL-1β and caspase-1 expression in the cells and culture supernatants were analyzed by Western blotting and enzyme-linked immunosorbent assay, and cell death was analyzed by lactate dehydrogenase assay. Stimulation of THP-1 macrophage-like cells with every periodontopathic bacteria induced IL-1β secretion without cell death, which was suppressed by the NLRP3 inhibitor, MCC950, and caspase-1 inhibitor, z-YVAD-FMK. Glyburide treatment suppressed IL-1β expression in culture supernatants and enhanced intracellular IL-1β expression, suggesting that glyburide may have inhibited IL-1β secretion. Subsequently, a periodontitis rat model was generated by injecting periodontal bacteria into the gingiva, which was analyzed histologically. Oral administration of glyburide significantly suppressed the infiltration of inflammatory cells and the number of osteoclasts in the alveolar bone compared with the control. In addition to glyburide, glimepiride was shown to suppress the release of IL-1β from THP-1 macrophage-like cells, whereas other sulfonylureas (tolbutamide and gliclazide) or other hypoglycemic drugs belonging to the biguanide family, such as metformin, failed to suppress IL-1β release. Our results suggest that pharmacological targeting of the NLRP3 pathway may be a strategy for suppressing periodontal diseases.